ENGINEERED CEMENTITIOUS COMPOSITES AS A HIGH-PERFORMANCE FIBER REINFORCED MATERIAL: A REVIEW (GEOMATE Journal, 2023)
Cementitious composites are one of the world's most consumed infrastructure construction materials because of their abundant resources, mature production process, and strong adaptability. Most of these materials, however, remain brittle. It highlights the need to develop low-cost, high-ductility cementitious materials for structural applications. These issues are the fundamental driving force behind Engineered cementitious composites (ECC) development due to the micromechanical interactions between its constituents and processing techniques. ECC is a high-performance, ultra-ductile fiber-reinforced cementitious composite material designed for high material volume and cost-sensitive applications in the construction sector. However, this material still lacks standardization regarding mix proportion and fiber used as a proper processing technique to balance economy and requirements for strength and durability. This paper aims to review some of the past researchers' design proportions and fiber types used as a reference and guide for future researchers utilizing ECC in their studies. This paper also covers ECC's results and target application in structural engineering.